The role of number words: the phonological length effect in multidigit addition. - Klessinger, Nicolai; Szczerbinski, Marcin; Varley, Rosemary (Memory & Cognition, 2012)
We explored the role of phonological representations of number words in exact calculation. The reaction times and accuracy of responses in multidigit addition problems were compared across three groups of participants (young healthy, older healthy, and 3 patients with severe aphasia) and two types of addition problems: phonologically long in English (containing the bisyllabic number word 'seven') and short in English (monosyllabic number words-e.g., 'six'). Older healthy participants were significantly faster and more accurate in calculation than younger healthy participants. The older participants showed no evidence of a phonological length effect. However this effect was apparent in the younger adults, with longer reaction times on phonologically long problems. Furthermore, there was an association between the presence of a phonological length effect and the overall speed of response, suggesting that less proficient calculators were more reliant on phonological mediation of performance. The aphasic participants retained the ability to complete multidigit additions and were as accurate as the younger healthy group, although the response times of two of the 3 patients were slow. The aphasic participants varied with regard to the presence of a phonological length effect. Two participants showed no evidence of phonological mediation, while 1 displayed a phonological length effect. The results suggest that language resources are not mandatory for exact addition, although they may be used to scaffold math performance in less competent calculators. Evidence of phonological mediation of performance in aphasic participants may provide insight into the integrity or otherwise of inner speech in severe aphasia.